Estnisk konst och konsthantverk. - Helme, Sirje; Mälk, Kadri (Stockholm : Yrwing Kunsthandel, 2001)
Kask, Jüri ; Keerend, Avo ; Lapin, Leonhard ; Meel, Raul ; Runge, Sirje ; Tolts, Andres ; Vint, Mare ; Mälk, Kadri ; Margus, Eve ; Sarapuu, Tiina ; Käsper, Eeva ; Kask, Alice ; Eelma, Kaarel ; Jänes, Heidy ; Kreem, Helena ; Õunapuu, Kristel ; Kukk, Jaana
Estnisk konst och konsthantverk, Galleri Tersaeus, Stockholm ; Dansens Hus, 20.06 - 17.07.2001
Zweeds
kunstcatalogus
Keywords: Estland